Perlindungan Hukum terhadap Perempuan Korban Kekerasan Dalam Rumah Tangga (KDRT) pada Tingkat Penyidikan berdasarkan Undang-Undang No. 23 Tahun 2004 tentang Penghapusan Kekerasan Dalam Rumah Tangga (UUPKDRT) - Karenina Aulery Putri Wardhani (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. Family is the smallest social unit in society that plays a role and has a huge influence on the social development and personality development of each family member. Tensions between husband and wife and parents with children are natural in a family or household, but it becomes unnatural to resolve the conflict using violence. Such behavior can be said in acts of domestic violence (DV). Indonesia also actually has regulations governing the matter in Law No. 23 of 2004 on the Elimination of Domestic Violence (EDV), but cases of domestic violence continue to increase every year, especially in Manado City. This thesis will discuss about how to Protect Women Victims of DV at the Investigative Level in Manado City Based on Law No. 23 of 2004 on the EDV. The writing of this thesis uses qualitative method as its research methodology. The data obtained is then analyzed qualitatively. The specifications used are descriptive analysis that describes comprehensively the Protection of Women Victims of DV at the Level of Investigation in Manado City Based on Law No. 23 of 2004 on the EDV. The conclusion of the study mentioned that the Female Individual Factor, domestic violence is very potentially greater if often quarrel with a partner. Couple Factor, DV is very potential if our partner or we have a relationship with another partner. Economic factors, can trigger the occurrence of no criminal violence against women in the family. In this case, the researchers noticed that one of the triggers was also but was not directly expressed by his wife by refusing to take money at the ATM for the next reason still taking care of the toddler. Socio-Cultural Factors, the occurrence of domestic violence is quite large but does not affect the decision of the victim to report the violence he received to the police. Verdict number 121/Pid.Sus/2020/PN.Mnd. Theform of protection received by the victim is from medical personnel as evidenced by Visum Et Repertum No.B/287/VIII//2019/Rs.Bhay which was made and signed by Doctor Jeane resulting in bruises. The police who conduct investigations and investigations to obtain preliminary evidence are not criminal and make arrests and arrests to suspects. The Court Judge who provides protection in the form of the implementation of the trial and adjudicating that the defendant has been proven legally and convincingly guilty of committing no